Comparative study on punishment and prevention methods of baby dumping: Malaysian perspectives - Termizi, Mazbah; Abdullah , Nor Hidayah; Mohd Jaafar, Noor Ismawati; Tagaranao, Mariam Saidona; Mohd. Safian, Yasmin Hanani (International Journal of Technical Reseach and Application, 2014)
Baby dumping case is a serious crime in Malaysia. The study is important to be conducted in order to discuss the suitable punishment with regards to this crime. It is not only confined to the legislations, but also to find the other preventive methods for the solution. In Malaysia, not only the laws are being used, but other preventive methods are also available such as the awareness, monitoring actions and baby hatch. This paper is to discuss the comparative study of the punishment and preventive methods available in Malaysia and some other countries. The method of this research is by using content analysis, under qualitative method, which the laws from various countries pertaining to baby dumping will be analyzed. By comparing Malaysia and other countries approach, we could have foreseen that the preventive methods are also needed as much as the punishment methods in order to curb the problem of baby dumping in Malaysia.